Identifikasi Faktor – Faktor Yang Memengaruhi Keberhasilan Usaha Kopi Jantan Toraja (Studi Kasus Pada UMKM Kopi 1000 Nurhidayah) - Dwi Prasetyawati Thana; Gidion Aryo Nugraha Pongdatu; Agustinus Mantong; Hariadi Hariadi (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2021)
A source of income for farmers would be 'Kopi Jantan Toraja' (Peaberry coffee). The growing demand due to changes in the lifestyles of people makes today's coffee more popular. 'Kopi Jantan Toraja' is one of the interesting business options to be produced to boost the farmers' economy. This study aims to define and evaluate the internal and external factors of the